Transformasi Padanan Kata Bahasa Indonesia Dalam Tren Konten Tiktok - Silvira; Mimi Rosadi (Ikatan Dai Indonesia, 2025)
This study examines the transformation of Indonesian equivalents that appear in content trends on the TikTok social media platform. The development of digital technology and the increasing use of social media have given rise to new forms of language use, including in terms of equivalents. This study aims to identify and describe how Indonesian equivalents undergo transformation in the context of creative content on TikTok. In the study, there is a problem identification to clarify the details of the problem, based on the formulation above, the problem identification in this study is as follows: Many foreign terms or new terms are used in TikTok content that do not have official equivalents in Indonesian. The use of equivalent words in TikTok content is often not in accordance with Indonesian language rules. Lack of awareness of social media users, especially TikTok users, regarding the importance of using good and correct Indonesian. The method used is a descriptive qualitative method with data collection techniques through observation and documentation of trending TikTok content in a certain period. The analysis was carried out by tracing the use of words that experienced changes in meaning, expansion of meaning, or the creation of new equivalents that differ from standard rules. The results of the study show that trends on TikTok encourage the formation of variations in equivalent words that are influenced by user creativity, popular language styles, and the need for expressions that are relevant to digital culture. These findings indicate that social media plays a role as a dynamic space in the formation and transformation of the Indonesian language in the modern era.